2021
DOI: 10.3389/fimmu.2021.669339
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccines: Current Understanding on Immunogenicity, Safety, and Further Considerations

Abstract: The world has entered the second wave of the COVID-19 pandemic, and its intensity is significantly higher than that of the first wave of early 2020. Many countries or regions have been forced to start the second round of lockdowns. To respond rapidly to this global pandemic, dozens of COVID-19 vaccine candidates have been developed and many are undergoing clinical testing. Evaluating and defining effective vaccine candidates for human use is crucial for prioritizing vaccination programs against COVID-19. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
99
0
9

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 80 publications
8
99
0
9
Order By: Relevance
“…Meanwhile, our ndings revealed that Sinovac had a 12 times lower correlation with side effects. The side effects after the second dose were more with the P zer-BioNTech vaccine, which correlates with the reported data that the systemic side effects of this type of vaccine tend to increase with the second dose [30]. Although several countries have suspended the Oxford-AstraZeneca (ChAdOx1-S) vaccine, especially among younger people, due to reports of vaccineinduced immune thrombocytopenic thrombosis [31], the public in Malaysia has received this vaccine considering the bene ts are outweighed the risks of the disease.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Meanwhile, our ndings revealed that Sinovac had a 12 times lower correlation with side effects. The side effects after the second dose were more with the P zer-BioNTech vaccine, which correlates with the reported data that the systemic side effects of this type of vaccine tend to increase with the second dose [30]. Although several countries have suspended the Oxford-AstraZeneca (ChAdOx1-S) vaccine, especially among younger people, due to reports of vaccineinduced immune thrombocytopenic thrombosis [31], the public in Malaysia has received this vaccine considering the bene ts are outweighed the risks of the disease.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the differences in the intensity and pattern of side effects could be attributed to the difference in vaccine type as reported previously in comparing potential COVID-19 vaccine candidates [30]. Notably, preliminary reports on the differences between COVID-19 vaccine candidates indicated that Sinovac vaccines might be associated with approximately ve times fewer side effects than the other two tested vaccines [30]. Meanwhile, our ndings revealed that Sinovac had a 12 times lower correlation with side effects.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Non-human adenovirus strains are not subject to pre-existing host immunity (e.g., AZD1222), as the vector virus normally only affects chimpanzees. However, in principle, adjuvants deserve attention regarding vaccine-derived skin toxicity, as these agents bear the capacity to drive off-target inflammatory reactions [ 16 ]. After all, the skin is commonly involved in vaccine-derived adverse reactions [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The differences are more pronounced between vaccines from different platforms. Recently, we analysed the neutralizing antibody data for vaccinated and convalescent sera, deducing the ratios of NAb GMTs of vaccinated sera to convalescent sera [ 14 ]. The results of the analysis revealed that vaccinated/convalescent ratios of inactivated vaccines fall in the range of 0.27–1.11, which are relatively lower than those of other vaccine candidates which fall between 1.41 and 4.13.…”
Section: Introductionmentioning
confidence: 99%